Purchase Intentions of Electric Vehicles: An Exploration of Trends, Theories and Determinants - Timilsina, Jagadish (BIC Journal of Management, 2025)
Global selection of electric vehicles (EVs) will market endurable motility and help in the lowering of greenhouse gas emissions. However, the consumption of EVs is being delayed by various factors, like consumer resistance, infrastructure lack, and technological limitations. This study connects a complete comprehension of an individual’s behaviour and market scenario to the trends, theories, and factors that increase EV purchase intentions. To combine theoretical frameworks, such as the Theory of Planned Behaviour (TPB), the Technological Acceptance Model (TAM), and the Norm Activation Model (NAM), with empirical research, an integrative review of the various literature was conducted. To determine their impact on the adoption of EVs, several key factors were examined, including perceived behavioural control, financial incentives, social norms, environmental concern, and technological readiness. This review concentrated on consumer intentions of buying, which are affected by various related forces. A significant influence of concern towards the environment and control of perceived behaviour has been seen in EV selection, whereas incentives and cost considerations play a pivotal role in decision making. During the willingness to shift towards EV, technological readiness and social norms play a moderating part. This review focuses on the identification of gaps in existing research, particularly in mediating and moderating factors affecting EV adoption. Prioritisation in expanding the infrastructure of charging, incentives, and exploiting the influence of society to enhance EV adoption needs to be done by stakeholders and policymakers. Environmental benefits, technological advancements, and cost-saving marketing strategies need to be emphasised to appeal to diverse consumer segments. This study plays a part in the structural framework for understanding intentions of EV purchase, integrating behavioural theories and empirical findings. It provides applied understanding to governments, manufacturers, and marketers to transform the shift towards sustainable mobility.